THE EFFECT OF GIVING CUCUMBER JUICE ON HIGH BLOOD PRESSURE IN PREGNANT WOMEN IN THE WORKING AREA OF PONDOK TINGGI PUBLIC HEALT CENTER, SUNGAI PENUH CITY IN 2022 - Sesmi Nanda Oktavia; Armita Sri Azhari; Eza Meydia (Ensiklopedia of Journal, 2023)
Based on the background, the problem in this study is "how is the effect of giving cucumber juice on high blood pressure in pregnant women".High blood pressure that occurs during pregnancy is a condition of pregnant women who experience blood pressure that is above 140/90 Mmhg. During pregnancy, there are two types of hypertension, namely chronic hypertension and hypertension in pregnancy. The purpose of the study was to determine the difference in the average blood pressure of pregnant women before and after administration of cucumber juice. This type of research uses a Pre Experiment one group Pre-Post Test Design. Subjects were 28 pregnant women with systolic blood pressure above normal. The data collection tool used an observation sheet, the subject then got 250 grams of cucumber juice for 7 days. The research design used Quasy Experiment with Pre-test Post-test Control Group Design. Sampling technique with total sampling. A sample of 28 pregnant women. The instrument used is an observation sheet. The data analysis technique used paired t-test with 0.05. The results showed that before giving cucumber juice to pregnant women, as many as 28 pregnant women experienced high blood pressure. After giving cucumber juice to pregnant women, 15 pregnant women experienced changes in blood pressure to normal and 13 pregnant women experienced mild hypertension. From the independent T-test, the results obtained P-Value = 0.000 < (0.05) so that Ha is accepted. The conclusion of this study is that there is an effect of giving cucumber juice to pregnant women who experience high blood pressure in the working area of the Pondok Tinggi Public Health Center, Sungai Penuh City in 2022.